Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1118/1.4730500
|View full text |Cite
|
Sign up to set email alerts
|

Sub-second high dose rate brachytherapy Monte Carlo dose calculations withbGPUMCD

Abstract: bGPUMCD has the potential to allow for fast MC dose calculation in a clinical setting for all phases of HDR treatment planning, from dose kernel calculations for plan optimization to plan recalculation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Recently, accelerated MC computation using graphics processing units (GPUs) has been employed in radiotherapy research and clinical applications due to GPU’s tremendous parallel processing capability at a low cost (Jia et al ., 2014). Substantial acceleration factors over conventional CPU-based computations have been reported for photon, electron and proton dose calculations (Jia et al ., 2010a; Jia et al ., 2011; Hissoiny et al ., 2011; Jahnke et al ., 2012; Townson et al ., 2013; Bol et al ., 2012; Hissoiny et al ., 2012; Jia et al ., 2012a; Yepes et al ., 2010; Badal and Badano, 2009; Ma et al ., 2014; Tseung et al ., 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Recently, accelerated MC computation using graphics processing units (GPUs) has been employed in radiotherapy research and clinical applications due to GPU’s tremendous parallel processing capability at a low cost (Jia et al ., 2014). Substantial acceleration factors over conventional CPU-based computations have been reported for photon, electron and proton dose calculations (Jia et al ., 2010a; Jia et al ., 2011; Hissoiny et al ., 2011; Jahnke et al ., 2012; Townson et al ., 2013; Bol et al ., 2012; Hissoiny et al ., 2012; Jia et al ., 2012a; Yepes et al ., 2010; Badal and Badano, 2009; Ma et al ., 2014; Tseung et al ., 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Compared with previous work on GPU-based fast MC dose calculation, [12][13][14][18][19][20] this study does better job on "fair comparison." Instead of comparing GPU code with serial CPU code, this study makes multithreaded CPU code and conducts a fairer comparison of GPU and CPU.…”
Section: B Comparison With Previous Workmentioning
confidence: 93%
“…19 Hissoiny et al reported a GPU based brachytherapy dose calculation tool using a precalculated phase space file (PSF) as input and achieved ∼2 s speed for a preoptimized plan. 20 However, electron transport was absent from their MC code and they did not consider external beam radiotherapy. Townson et al reported a GPU dose calculation engine for IMRT, 21 in which they used "phase-space-let" method to calculate dose distribution from a patient-independent PSF.…”
Section: Introductionmentioning
confidence: 99%
“…For example, MC calculation times have been reported that range from subminute to a few minutes for low-dose-rate brachytherapy applications, 32-34 from 2.5 to 17.0 min for 40 3 - 140 3 2-mm voxels, respectively, for an HDR rectal application, 35 and from subsecond for a single source to a couple of seconds for an HDR plus shield implant using graphics processing unit implementation. 36 …”
Section: The Monte Carlo Simulation Methodsmentioning
confidence: 99%